Agreement between the Caribbean Community (CARICOM) and the World Organisation for Animal Health (OIE) (2012)
Presents the text of the agreement between CARICOM and OIE which aim to collaborate to prevent the spread of animal diseases, to improve animal health and to harmonise regulations for trade in animals and animal products in CARICOM countries.
Keywords: ANIMAL HEALTH